2018
DOI: 10.1186/s12872-018-0830-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel ultrafast-low-dose computed tomography protocol allows concomitant coronary artery evaluation and lung cancer screening

Abstract: BackgroundCardiac computed tomography (CT) is often performed in patients who are at high risk for lung cancer in whom screening is currently recommended. We tested diagnostic ability and radiation exposure of a novel ultra-low-dose CT protocol that allows concomitant coronary artery evaluation and lung screening.MethodsWe studied 30 current or former heavy smoker subjects with suspected or known coronary artery disease who underwent CT assessment of both coronary arteries and thoracic area (Revolution CT, Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This study was designed to test the equivalence of the combined cardiac and lung CT protocol vs. conventional cardiac CT protocol with Δ = 15% on the basis of previous observations 6 . Sample size calculation was performed at time of study design in order to avoid any “ post-hoc ” power calculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was designed to test the equivalence of the combined cardiac and lung CT protocol vs. conventional cardiac CT protocol with Δ = 15% on the basis of previous observations 6 . Sample size calculation was performed at time of study design in order to avoid any “ post-hoc ” power calculation.…”
Section: Methodsmentioning
confidence: 99%
“…We recently proposed a CT protocol for the simultaneous screening of CAD and lung cancer in those subjects who are deemed to be at high risk for the two conditions 6 . Our preliminary data obtained from 30 subjects showed that the new protocol reliably allows concomitant cardiac and lung CT scanning, thus avoiding to double the doses of radiation and contrast dye which are used when two distinct examinations are performed to study the coronary arteries and the pulmonary areas.…”
Section: Introductionmentioning
confidence: 99%